Legal Implications of the Sale and Purchase of Land Rights Underhand in Demak Regency (Study of Decision No. 34/Pdt.G/2020/PN. Dmk) - Muslichah, Siti (Jurnal Konstatering, 2024)
It is undeniable that in everyday life, there are still many land sales and purchases carried out underhand, not in the presence of an authorized official, namely a Notary/PPAT. This study aims to analyze the legal implications of the sale and purchase of land rights underhand in Demak Regency (Study of Decision No. 34/Pdt.G/2020/PN. Dmk). The type of research used in this thesis is normative legal with a case approach. This approach method uses a normative legal approach or written legal research. The types and sources of data used are secondary data. Data collection methods are literature research and documentation studies. The data analysis method used in analyzing the data is qualitative analysis, namely the data obtained is then analyzed qualitatively to achieve the objectives. The results of the study show that in the concept of legal certainty, it can be made in writing in the form of an agreement before an authorized official and recognized by the state, so that it has perfect legal force before the court. In accordance with Article 37 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration. A sale and purchase agreement made underhand is difficult to prove if a legal act of transferring land rights has occurred. Therefore, legal protection is needed, namely repressive legal protection and preventive legal protection.